Предмет: Алгебра,
автор: фасолинка1
Решите уравнение: -0,6(3+2,5х)=-1,5(2х-1)-2
Приложения:
Ответы
Автор ответа:
1
..................................................
Приложения:
Автор ответа:
0
-0,6(3+2,5х)=-1,5(2х-1)-2
-1,8-1,5х=-3х+1,5-2
-1,5х+3х=1,3
1,5х=1,3
х=0,86
-1,8-1,5х=-3х+1,5-2
-1,5х+3х=1,3
1,5х=1,3
х=0,86
Похожие вопросы
Предмет: Английский язык,
автор: krokodil1744
Предмет: Литература,
автор: sanihanmeruert09
Предмет: Алгебра,
автор: milkiswww
Предмет: Математика,
автор: 79856287654егпывл
Предмет: Математика,
автор: Аноним